EKSTRAKSI DATA INDEKS VEGETASI UNTUK EVALUASI RUANG TERBUKA HIJAU BERDASARKAN CITRA ALOS DI KECAMATAN NGAGLIK KABUPATEN SLEMAN YOGYAKARTA - Iswari Nur Hidayati (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2013)
The population growth is make conversion of green space area to be settlement. This situation supports degradation of environmental quality in urban areas whereas the function of urban forest is affecting the surrounding air directly or indirectly by altering the atmospheric conditions. Conversion of green space area to non-green green space area is a frequently encountered problem lately. Therefore, this research showed that relationship between vegetation index with urban green space. The objectives of this research are: (a) to assess the ability of remote sensing data especially ALOS AVNIR-2 imagery for extraction of vegetation density through vegetation index analysis, (b) to analyze the availability of green space using remote sensing data; and (c) to analyze the density of vegetation on land-use planning based on Urban Land Use Planning (RDTRK) in Ngaglik District.This study was conducted in Ngaglik area using ALOS imagery ANVIR-2 recording in 2009. Distribution of green open space transformation used Normalized Difference Transformation Index (NDVI) and RDTRK documents. The results of this study indicated that urban green space and NDVI can be extracted using ALOS AVNIR-2 imagery. The formula of NDVI was 188.1 x (NDVI)) -0.5617. The vegetation densities can be divided into five classes, non-vegetated area was 13,398,739.48 m² (34.24%), very low vegetation density was 5,381,133.12 m² (13.75%), low vegetation density was 8,143,116.62 m² (20.81%), medium vegetation density was 10,022,040.95 m² (25.61%), high vegetation density was 1,878,236.10 m² (4.80%), and very high vegetation density was 7181.22 m² (0.02%). The area of green open space was in conformity with the laws in force in the amount of 25.480.722 m² (64.86 %).